THE EFFECT OF LABOR AND WORK SKILLS ON WORK PRODUCTIVITY OF PT MANNA HANNA ENERGI BOGOR WEST JAVA - Widya Hastuti; Rushadiyati; Nurminingsih (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
This study aims to examine the effect of labor and work skills on employee productivity at PT Manna Hanna Energi. This research is a type of descriptive quantitative research where the data used in this study are qualitative data. The study population included 60 employees of PT Manna Hanna Energi. Data collection using questionnaires, data analysis techniques used in this study using descriptive statistical analysis while the method of analysis used in this study is PLS (Partial Least Square) using SmartPLS version 3.0.m3. The results showed that Labor has a positive and significant effect on Work Productivity. This shows that the effect of labor on work productivity is significant. Moreover, Labor has a positive and significant effect on Work Skills. This shows that the effect of labor on work skills is significant. Meanwhile, work skills have a positive and significant effect on work productivity. This shows that the influence between Work Skills and Work Productivity is significant.